Human Trafficking : Interdisciplinary Perspectives - Burke, Mary C; Burke, Mary C. (New York Routledge, 2018)
With a range of experts from different disciplines and professions, this text comprehensively explains human trafficking as it exists and is being addressed in the twenty-first century. The first section gives an overview of the issue and contextualizes it within a human rights and historical framework. The second section provides the reader with more detailed, interdisciplinary information about trafficking. The third section, which contains a chapter written by a former FBI agent, focuses on the anti-trafficking movement and addresses international responses to the problem, as well as considerations for working with victims. Human Trafficking closes with a chapter about how trafficking is being addressed and how individuals, larger social groups, and organizations can get involved in putting an end to the crime and to helping survivors. Human Trafficking is essential reading for professionals in law enforcement, human services, and health care, and for concerned citizens interested in human rights and making a difference in their communities. This book is also intended for use in undergraduate and graduate interdisciplinary courses in human trafficking.
Section I: Human Trafficking Explained. -- 1. Introduction to Human Trafficking: Definitions and Prevalence / Mary C. Burke and Brian Bruijn -- 2. Historical Perspective: Slavery over the Centuries / Brooke N. Newman. -- Section II: A Closer Look. -- 3. Sociological Perspective: Underlying Causes / Marci Cottingham, Thomas Nowak, Kay Snyder, & Melissa Swauger -- 4. Fear, Fraud, and Frank Complexities: The Influence of Gender on Human Trafficking / Lisa C. Ruchti -- 5. Making Money out of Misery: Trafficking for Labor Exploitation / June Kane -- 6. Common Forms: Sex Trafficking / Kimberly McCabe -- 7. The Exploitation Equation: Distinguishing Child Trafficking from Other Types of Child Mobility in West Africa / Anne Kielland -- Section III: The Anti-Slavery Movement -- 8. Domestic and Foreign Policy Responses to the Problem of Human Trafficking / Sandi DiMola and Allyson Lowe -- 9. Victim Protection Policy in a Local Context: A Case Study / Patrizia Testaì -- 10. International Development Issues and Other Push Factors That Contribute to Human Trafficking / Jamie Turek and Lynsie Clott -- 11. The Human Security Framework: The Best Security Approach to Preventing and Combating Human Trafficking / Lynsie Clott -- 12. Law Enforcement Considerations for Human Trafficking / Bradley Orsini -- 13. Combatting Sex Trafficking through the Prosecution of Traffickers / Michael J. Frank and G. Zachary Terwilliger -- Section IV. Supporting Survivors 14. Mental Health Care: Human Trafficking and Post-Traumatic Stress Disorder / Veronica M. Lugris, Mary C. Burke and Leah Russell Flaherty -- 15. Human Trafficking and its Contribution to the Globalization of Infectious Diseases: Implications for Victims and Health Care Providers / Nicole Travis and Nurlanbek Sharshenkulov -- 16. Addressing the Problem: Community-Based Responses and Coordination / Judy Hale Reed.
Includes bibliographical references (pages 379-387) and index.
Text in English.
Keywords: Human trafficking; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Sociology; Human trafficking